Islam and Egyptian higher education: student attitudes - Cook, Bradley J. (Comparative education review, 2001)
To examine the nexus between Islam and education in Egypt, a sample of 381 university students in Cairo were surveyed about their feelings toward the role of Islam in the state-sponsored universities and in the Egyptian national curriculum. (DSE/DÜI)